Determinants of quality of life in individuals with chronic low back pain: a systematic review - Aleena Agnus Tom; Eslavath Rajkumar; Romate John; Allen Joshua George (Health Psychology and Behavioral Medicine, 2022)
Objective Chronic low back pain (CLBP) is a prominent medical condition that can affect an individual at some point in their life time which could lead to poor quality of life (QOL). Low back pain has affected approximately 577 million individuals globally by 2017. The aim of the current systematic review is to synthesise the existing evidence on the factors influencing the QOL in individuals with CLBP and to identify strategies to improve their QOL. Method PubMed, ScienceDirect, PsychNet and Google Scholar were used to extract studies reporting quantitative relationships between QOL and its possible determinants in individuals having CLBP and the intervention strategies to improve QOL. Results 10,851 studies were initially identified and twenty-six studies which met the inclusion criteria were selected for the review. 21 studies reported relationship between QOL and potential determinants and five studies assessed the influence of interventions on QOL. Determinants were classified as kinesiophobia, fear avoidance belief, or pain belief; occupation-related factors; pain and disability; activity; personal factors including age, gender, employment status; and other psychological factors including anxiety, quality of sleep, and health locus of control. Intervention strategies including MBSR, Pilates method and Back School Programme improved QOL in individuals with CLBP. Conclusion Psychosocial factors as well as the physical status of the individual contributed to the QOL in individuals having CLBP.